Quantum mechanics - Bransden, B. H.; Joachain, C. J. (New Delhi: Pearson Education, 2000)
This book gives a modern, comprehensive introduction to the principles of quantum mechanics, to the main approximation methods and to the application of quantum theory to a wide variety of systems. The needs of students having an average mathematical ability are kept very much in mind, with the avoidance of complex mathematical arguments and any undue compression of material.
Index 793-803p.
Keywords: Quantum mechanics; Quantum Physics; Physics